The entry of nanoparticles into solid tumours - Sindhwani, Shrey; Syed, Abdullah Muhammad; Ngai, Jessica; Kingston, Benjamin R.; Maiorino, Laura; Rothschild, Jeremy; MacMillan, Presley; Zhang, Yuwei; Rajesh, Netra Unni; Hoang, Tran; Wu, Jamie L. Y.; Wilhelm, Stefan; et al. (Nature materials, 2020)
The concept of nanoparticle transport through gaps between endothelial cells (inter-endothelial gaps) in the tumour blood vessel is a central paradigm in cancer nanomedicine. The size of these gaps was found to be up to 2,000 nm. This justified the development of nanoparticles to treat solid tumours as their size is small enough to extravasate and access the tumour microenvironment. Here we show that these inter-endothelial gaps are not responsible for the transport of nanoparticles into solid tumours. Instead, we found that up to 97% of nanoparticles enter tumours using an active process through endothelial cells. This result is derived from analysis of four different mouse models, three different types of human tumours, mathematical simulation and modelling, and two different types of imaging techniques. These results challenge our current rationale for developing cancer nanomedicine and suggest that understanding these active pathways will unlock strategies to enhance tumour accumulation. The dominant mechanism of nanoparticle entry into solid tumours has now been shown to be an active trans-endothelial pathway rather than the currently established passive transport via inter-endothelial gaps.